"Pretty as a Picture": The Aesthetics of the Picturesque in British Travel Accounts of Tunis (1835–1887). Issue 1 (1st June 2021) - Gannouni Khemiri, Imene
Abstract: Recently, there has been an upsurge of interest in travel writing, postcolonialism, and landscape politics. However, studies of travel writing addressing the notion of the picturesque have not yet explored the idea of aesthetic sensibility in British travel narratives in the Regency of Tunis. This article examines the aesthetics of the picturesque in three British travel accounts: Grenville Temple's Excursions in the Mediterranean : Algiers and Tunis (1835); Robert Lambert Playfair's Travels in the Footsteps of Bruce in Algeria and Tunis (1877); and Henry Spencer Ashbee and Alexander Graham's Travels in Tunisia (1887). These travelers used the picturesque in different but interlinked ways; they oscillated between finding the uncanny landscape an object of delight where it conformed to British aesthetic doctrine and an object of derision where they noted aesthetic deficiencies. By the turn of the nineteenth century, this picturesque way of seeing shifted into an Orientalist desire for "Otherness."